A Governor's Raj : British Administration during lord Irwin's Viceroyalty, 1926-1931 - Macnamara Michael Fenwick (New Delhi : Sage Publications, 2014)
Reveals the influence and role of Provincial Governors in Vice-Regal policymaking, affecting administration and governance of British India!
include index.
Keywords: History; HISTORY - Asia - India and South Asia; British colonies